2020
DOI: 10.1155/2020/4374801
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genome Sequencing and Phylogenetic Analysis of Two Dracocephalum Plants

Abstract: Dracocephalum tanguticum and Dracocephalum moldavica are important herbs from Lamiaceae and have great medicinal value. We used the Illumina sequencing technology to sequence the complete chloroplast genome of D. tanguticum and D. moldavica and then conducted de novo assembly. The two chloroplast genomes have a typical quadripartite structure, with the gene’s lengths of 82,221 bp and 81,450 bp, large single-copy region’s (LSC) lengths of 82,221 bp and 81,450 bp, and small single-copy region’s (SSC) lengths of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…In this study, SSR and long repeat analyses of plastomes showed variations among Garcinia species and varieties of G. mangostana . This supports that both molecular markers are useful for species identification and taxonomic studies 6264 .…”
Section: Discussionsupporting
confidence: 77%
“…In this study, SSR and long repeat analyses of plastomes showed variations among Garcinia species and varieties of G. mangostana . This supports that both molecular markers are useful for species identification and taxonomic studies 6264 .…”
Section: Discussionsupporting
confidence: 77%
“…The DNA samples were then subjected to quality and quantity checks using 1% agarose gel electrophoresis and spectrophotometric methods measured by a Nanodrop ND1000 spectrophotometer [19]. High-quality cp DNA was used to prepare a library with an insert size of 350 bp, which was then sequenced on an Illumina Novaseq platform [20] at Nanjing Genepioneer Biotechnologies Inc. (Nanjing, China).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“… 2003 ; Yao et al. 2020 ). The IR sizes of published Phalaenopsis plastid genomes are 24,719 ( P. lobbii ) (Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, the complete plastid genome of P. zhejiangensis is only 143,574 bp in length, which turns out to be the smallest among all known cp genome sequences in genus Phalaenopsis. The cp genomes of most flowering plants range from 120 kb to 160 kb, and the difference in genome size is mainly caused by contraction and expansion of the IR region (Goulding et al 1996;Ingvarsson et al 2003;Yao et al 2020). The IR sizes of published Phalaenopsis plastid genomes are 24,719 (P. lobbii) (Wang et al 2019) to 25,846 bp (P. equestris) (Jheng et al 2012).…”
Section: Discussionmentioning
confidence: 99%